FOUR RECENT PHREATIC ERUPTIONS OF TURRIALBA VOLCANO (2010-2013) ONE PER YEAR - Duarte-González, Eliécer Duarte González (2014)
Since mid-2005, Turrialba volcano began a growing gasification process after some seismic swarms registered, starting in 1996. This essay summarizes the main findings of four phreatic eruptions that occurred during the last four years (2010-2013) including; observations, documentation and geographical analysis of materials, characteristics of the proximal emplacement of solid materials as well as some observations of the impact of eruptions on the surrounding environment. Observation and documenting of physical changes enables the collection of perishable, short live information occurring on the volcano’s summit and vicinity, with the clear aim of fixing in time relevant facts that may be later compared with some other methodologies such as deformation, geochemistry and volcano seismology. Eventually and with the repetition of natural events and patterns of internal processes, the comparative analysis takes place. The four phreatic eruptions occurred during two different seasons: two at the end of the rainy season and two in the middle of the year, which makes the inter comparison even more interesting. Such described tasks are part of different methodologies carried out by the volcano surveillance team at the Observatorio Vulcanológico y Sismológico de Costa Rica (OVSICORI-UNA).